2013
DOI: 10.1242/jeb.079830
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress survival in the pre-adult stage of the life cycle in an intercontinental set of recombinant inbred lines ofDrosophila melanogaster

Abstract: SUMMARYIn insects, pre-adult stages of the life cycle are exposed to variation in temperature that may differ from that in adults. However, the genetic basis for adaptation to environmental temperature could be similar between the pre-adult and the adult stages of the life cycle. Here, we tested quantitative trait loci (QTL) for heat-stress survival in larvae of Drosophila melanogaster, with and without a mild-heat-stress pre-treatment. Two sets of recombinant inbred lines derived from lines artificially selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
2
18
1
1
Order By: Relevance
“…The QTL in the middle of chromosome 2 (Q2) was tested for field‐released adult flies, and flies carrying the QTL genotype for heat‐stress resistance were better at locating resources in field releases under high temperatures (Loeschcke et al., ). In addition, this QTL on chromosome 2 was also significant for EAS under heat stress in a laboratory experiment (Sambucetti et al., ), as in the present field study. An extensible list of many candidate genes was provided for Q2 in previous studies (Morgan & Mackay, ; Norry et al., 2007a, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The QTL in the middle of chromosome 2 (Q2) was tested for field‐released adult flies, and flies carrying the QTL genotype for heat‐stress resistance were better at locating resources in field releases under high temperatures (Loeschcke et al., ). In addition, this QTL on chromosome 2 was also significant for EAS under heat stress in a laboratory experiment (Sambucetti et al., ), as in the present field study. An extensible list of many candidate genes was provided for Q2 in previous studies (Morgan & Mackay, ; Norry et al., 2007a, ).…”
Section: Discussionsupporting
confidence: 81%
“…In this insect model, artificial selection on heat‐stress resistance changed both expression level of many genes and a subset of the constitutive proteome in adult flies in the laboratory (e.g., Sørensen et al., , ). QTL were also identified for survival after heat stress in the pre‐adult stage of the life cycle under standardized laboratory conditions (Sambucetti et al., ). However, studies on thermotolerance conducted under standardized laboratory conditions may not necessarily reflect the performance at varying temperatures of stress in the field (e.g., Kristensen et al., ; Loeschcke & Hoffmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as QTL ranges are wide and longevity QTL are abundant and widespread over all of the genome, we do not analyze across-studies colocalization of QTL in details. Regarding co-localizations between longevity and themotolerance QTL from previous studies, some longevity QTL colocalized with thermotolerance QTL in the same set of RIL used in the present study (Norry et al 2008;Sambucetti et al 2013). Interestingly, the 10A1-12E QTL for longevity detected at high temperature (30°C) in this study co-localized with a thermotolerance QTL identified in Norry et al (2008) with positive additive effects for both traits, indicating that the QTL conferring high KRHT also increased longevity at high temperature.…”
Section: Discussionsupporting
confidence: 64%
“…Given the well‐known association between longevity and fecundity, it is interesting to test these two classes of traits for their possible associations to heat‐resistance genotypes at elevated temperature (e.g., Loeschcke et al., ). QTL mapping in recombinant inbred lines (RIL) from crosses between heat‐selected populations provided information about genomic regions affecting heat resistance (Norry et al., , 2007a, ; Morgan & Mackay, ; Arias et al., ; Sambucetti et al., ), as well as longevity and fecundity (Defays et al., ; Sambucetti et al., ; Highfill et al., ). This information can be used to establish fly stocks with alternative genotypes for heat resistance, which can be used to test fitness‐related traits of individuals carrying heat‐sensitive genotypes in comparison to individuals carrying heat‐resistant genotypes (e.g., Loeschcke et al., ).…”
Section: Introductionmentioning
confidence: 99%